Immobilization of Pseudomonas aeruginosa FNCC-0063 on Calcium Alginate and Its Application as Bioabsorbent - Novianty, Iin; Suratman, Adhitasari; Mudasir, (Al-Kimia, 2023)
Biosorption of Cu (II) using bacteria Pseudomonas aeruginosa FNCC-0063 was immobilized on calcium alginate (PAI). This research examined the effect of various parameters such as pH, contact time, and initial Cu (II) concentration. The biosorption mechanism of Cu (II) was studied by sequential desorption with H2O, KNO3 1 M, HNO3 0.5 M and Na2EDTA 0.1 M. Cu (II) concentration was analyzed using atomic absorption spectrophotometer (AAS). The results showed that optimum Cu (II) ion biosorption occurred at a pH biosorption rate constant of 0.03724 g mg-1.min-1. The kinetics studies showed that Cu (II) biosorption follows pseudo-second-order. The biosorption capacities of 36.60 mg/g. Cu (II) Biosorption followed the Freundlich equation, as shown by a high correlation coefficient (R2) of about 0.99. Ionic bonds dominated the biosorption mechanism of Cu (II) ion on immobilized PAI.